SARCINA VENTRICULI-RELATED GASTRITIS: A RARE CASE OF GASTRIC INFECTION IN A PATIENT WITH DELAYED GASTRIC EMPTYING - KUMARI, PRIYA; DASH, MONICA; MOHAPATRA, PRADEEP KUMAR (International Journal of Current Pharmaceutical Research, 2024)
Sarcina ventriculi (SV), which is also called Clostridium ventriculi, is a rare, non-motile, aerobic, Gram-positive coccus that breaks down carbohydrates through fermentation. It thrives in acidic environments, making the human stomach a suitable habitat, particularly in conditions associated with gastric stasis. SV belongs to the Clostridiaceae family. Recent studies have implicated Sarcina ventriculi in severe gastrointestinal conditions, including emphysematous gastritis, pyloric stenosis, gastroparesis, gastric outlet obstruction, gastric perforation, and gastric adenocarcinoma. Increased awareness of this organism and further studies are essential to understanding its role in human disease.